De novo assembly of the Japanese lawngrass (Zoysia japonica Steud.) root transcriptome and identification of candidate unigenes related to early responses under salt stress - Xie, Qi; Niu, Jun; Xu, Xilin; Xu, Lixin; Zhang, Yinbing; Fan, Bo; Liang, Xiaohong; Zhang, Lijuan; Yin, Shuxia; Han, Liebao (Frontiers in Plant Science, 2015)
Japanese lawngrass (Zoysia japonica Steud.), an important warm-season type turfgrass, has an excellent characteristic that allows it to survive from infertile sands to calys and especially to grow well in salinity soils. However, little is known about its molecular mechanism involving in salt stress. Here, we used the high-throughput RNA sequencing (RNA-Seq) technology to explore the changes of gene expression of the zoysia grass under high concentration NaCl treatment. We firstly constructed two sequencing libraries, including a control samples (CK) and a NaCl-treated samples (Case), and sequenced them by using Illumina HisSeqtm2000. The resulting approximately 157.20 million paired-end reads and a total length of 68.68 Mb were obtained. Subsequently, 100,800 unigenes with a N50 length of 1,104bp were assembled by trinity, among which 70,127 unigenes were functionally annotated (e-value≤10-5) in the non-redundant (nr) protein database. Furthermore, three public databases, the Kyoto Encyclopedia of Genes and Genomes (KEGG), Swiss-prot, and the Cluster of Orthologous Groups(COG), were used for gene function analysis and enrichment. The annotated genes included 46 Gene Ontology (GO) terms, 120 Kyoto Encyclopedia of Genes and Genomes(KEGG) pathways, and 25 Clusters of Orthologous. Compared with control, 6035 genes showed significantly difference (false discovery rate≤0.01, ｜log2Ratio|≥1) in NaCl-treated samples. These genes were enrich in 10 KEGG pathways and 58 GO terms and subjected to 25 COG categories. Using high-throughput next-generation sequencing (NGS ) technology, we had built a database of global transcript resource for Z. japonica Steud roots. Result from our study also advance understanding of early salt response in roots of Japanese lawn.